Effect of Aerobic Exercises on Memory and Attention in Veterans with Post-Traumatic Stress Disorder - M. Moslehi; M. Shahbazi; E. Arabameri; Sh. Tahmasebi Boroujeni (Afarand Scholarly Publishing Institute, 2019)
Aims: Cognitive disorders is one of the problems of veterans with post-traumatic stress disorder (PTSD). The current study aimed at investigating the effects of aerobic exercises on memory and attention in veterans with PTSD. Materials & Methods: The present semi-experimental study with pre-test post-test design and control group was conducted in 2016 among 21 patients with PTSD, who were referred to Boostan Psychiatric Hospital in Ahvaz. The subjects were voluntarily selected through purposive sampling method and, then, randomly divided into two groups: aerobic exercise (n=11) and control (n=10) groups. The exercises were performed for 8 weeks, 3 sessions a week. Memory level was measured by Wechsler questionnaire and attention level was measured by strop test. The data were analyzed by SPSS 22, using dependent and independent t-tests. Findings: In the aerobic exercise group in the post-test stage, there was a significant difference between the mean scores of all Wechsler memory subscales and the level of attention (p<0.05), while there was no significant difference in the control group (p>0.05). There was a significant difference between the exercise group and the control group (p<0.05). Conclusion: Aerobic exercises are effective in improving memory performance and attention in patients with PTSD.